Effectiveness Log Evaluation of Ultra-Deep Carbonate Reservoirs Based on Multi-Scale Fracture-Cave Parameter - YIN Rong; SUI Xiuying; LAI Qiang; WANG Xiyu; WU Yiyu; YI Hongmei (Cejing jishu)
The ultra-deep carbonate reservoirs in member 2 of the Dengying formation in the Penglai gas area of the Sichuan basin exhibit lithological diversity, developed fractures and dissolution pores/caves, low matrix porosity, and strong heterogeneity. When evaluating reservoir effectiveness using single-scale fracture-cave parameters such as porosity and surface cavity ratio, mismatches often occur between actual test results and reservoir parameters. To address this issue, integrated analyses of core samples, conventional logging, electrical imaging logging, and array acoustic logging data are conducted to investigate controlling factors of reservoir effectiveness based on multi-scale fracture-cave parameters at borehole well and near-wellbore scales. After clarifying the controlling factors, the analytic hierarchy process (AHP) is employed to construct a reservoir quality factor integrating multi-scale fracture-cave parameters from borehole wall to near-wellbore domains, establishing a classification standard for reservoir evaluation in member 2 of the Dengying formation. Results demonstrate that effective reservoirs in the study area are primarily controlled by matrix porosity, surface cavity ratio, pore-cave connectivity index, and Stoneley wave energy attenuation coefficient. The classification standard based on reservoir quality factor and gas production per meter categorizes reservoirs into class I、Ⅱ、Ⅲ、IV, with class II and III reservoirs dominating in the target member 2 of Dengying formation. Verification through 11 tested intervals from 9 wells shows a 90.9% consistency rate in effective reservoir interpretation, providing reliable guidance for test zone selection in new wells within the study area.